Environmental awareness and green products consumption behavior: A case study of Sabah State, Malaysia - Sarimah Surianshah (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Surianshah S. 2021. Environmental awareness and green products consumption behavior: A case study of Sabah State, Malaysia. Biodiversitas 22: 2685-2692. The severe weather changes in the Sabah state of Malaysia have raised a great concern for us to address it through environmental awareness. Addressing the problem is important because Sabah is one of the main tourist destinations in Malaysia with its beautiful biodiversity, flora and fauna. Hence, this paper examines the level and relationship between environmental awareness and green product consumption behavior in Sabah. Here, we mainly measure environmental awareness using proxies of awareness towards climate change issues. A systematic questionnaire survey was conducted to 300 respondents of Sabah, including Tawau, Lahad Datu, Sandakan, and Kota Kinabalu. The descriptive statistics results show that people in Sabah have a high level of environmental awareness and green product consumption. In particular, they aware to conserve and preserve the tropical rainforest ecosystem and consume green products for future generations benefits. However, to note that there is still a low Sabahan's awareness about impact of overuse of natural resources and the importance of consuming green products in daily life. The estimate of the relationship between both variables shows a positive and statistically significant effect, especially in Kota Kinabalu. Also, the effect is pronounced when we address potential endogeneity bias in the baseline model. This study suggests that the government, policymakers, and youngsters continuously spread the benefits of green product consumption. This is because an increase in environmental awareness possibly helps mitigate environmental issues and lead to better biodiversity conservation and economic improvement in Sabah and Malaysia.